A contrastive analysis of processes in british and american political speeches in light of systemic functional grammar - Vũ Thị Bạch Trinh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
I find the arguments and implications in the political speeches of US Presidents and British Prime Ministers really motivating for this study, whose aim is to find out the manipulative use of language as well as the similarities and differences in linguistic features of the two corpora. At the meantime, the paper is also aimed at investigating how the Presidents and Prime Ministers use language to persuade public in order that its findings are, to a certain extent, applicable to teaching and learning English.